(untitled) (Bulletin KNOB, 1990)
A well-balanced planning policy aiming at the preservation of nature and environment has to include socio-historical values with respect to landscape. New governmental acts and notes such as the new Act of Monuments (1988) and the Fourth Note on Area Planning (1988) promote this sort of policy. The Regional Archeological Recording Project, an initiative of the Institute for Pre- and Protohistory of the University of Amsterdam traces archaeological sites in the rural area and advices municipal, provincial and state-institutions at their area planning policy with respect to socio-historical values. Human traces from pre-historic times on can be observed almost everywhere in Holland. Cultural, natural and landscape phenomena and their mutual relations tell about past processes. Parts of this archaeological heritage like dolmens and tumuli are visible. Not being characterized by spatial structures at the surface the largest part however is very hard to discover. Traces in the soil, which point at these invisible earlier settlements, form important sources of Information about the past as well. These archaeological discoveries represent Holland’s inhabitation history of the last 25.000 years and more. Their preservation depends on the administration of nature and landscape now and in the near future. Most of these discoveries cannot be seen at the surface and therefore are very vulnerable for unperceived destruction by cultural and civil-technical operations. The same counts for their landscape context. The department Protection of Monuments of the State Office for Archaeological Soil Research and the Central Archaeological Archives of the same office both contain Information on Holland’s soil archives. Here all valuable sites are subscribed in topographical maps scale 1:25.000. The legally protected monuments (about 1600) are meant to be preserved permanently and can be used for restoration and/or scientific research. Monuments in the so-called ’report’ areas are not protected, but municipalities are requested to comprise these sites in their development plans so that archaeological research could be executed in good time. The third category of ’attention’ areas knows no restrictions. In consultation with the landholder soil activities can be directed by archaeologists. Determination of the quality or value of the archaeological discovery generally happens in practice. At an archaeological site different discoveries can be made. Artefacts are all objects made by man. A large amount of objects can indicate a human settlement whereby the type of discovered artefacts like earthenware, metal and stone object defines this settlement as cemetery etc. Also organic remainders such as rests of wooden foundations or parts of animal and human skeletons form an important source of information. Soil tracks are caused by adaptations of this soil by man. Colour and structure differ from the surrounding grounds. By coupling several tracks, one can determine a larger unity like a house, a tumulus, a settlement and so on. (Bio)chemical residues like phosphate and zinc indicate human activity. Crystals of haemoglobin preserved in the soil or on tools supply Information on the type of man or animal as well as the history of genetics and certain diseases. The internal context is the network of relations between the various categories (fig. 1). The external context consists of the relation between archaeological locations and other sites together representing earlier societies. Nowadays pollution and souring threaten to ’dissolve’ all archaeological Information. Mapping and evaluation of the still present sites therefore is necessary. R.A.A.P. has developed a fast method of archaeological field-mapping in behalf of the preservation of sites and research of their possibilities at area planning. To be able to trace all unknown archaeological sites, experiments have been executed with systematic analysis of environmental characteristics. Also in pre-historic times functional and economical factors influenced the choice of locations. Understanding of these motives makes it possible to predict the discovery of still unknown sites. For that reason data of already known settlements are being worked up in the computer program of the Geographical Information System. Results of fieldwork and soil research will be rendered in reports with maps to direct regional area planning. R.A.A.P. also developed non-destructive research techniques to determine archaeological values. Geo-electric research can gauge the soil’s electric resistance. Measured values are transformed to readable images by a computer, which makes archaeological remainders visible. Magnetometer research reveals concentrations of stone, iron and earthenware. Phosphate-mappings detect centuries old inhabitation layers because of their accumulation of human and animal garbage. Drill-research is a fast way to discover present inhabitation tracks, while ecological mapping is used to determine the quality of the present material. Obliquely taken aerial surveys processed in special computer programs contain Information on subterranean phenomena. The chosen technique at field-mapping depends on the type of research, the condition of the soil and circumstances of preservation. All archaeological discoveries are vulnerable. They all loose information because they are exposed to certain breakdown processes. Therefore it seems logical to protect only those sites containing enough information for future research. Sites can also be protected for their visual or socio-historical value. After five years of field-mapping R.A.A.P. concludes that the number of discoveries increases in each region but the number of sites to be protected decreases at the same time. For irony wants that archaeological locations are damaged at the moment of discovery.